Church Members’ Perception of Returning Tithes in Paal 2 Seventh-Day Adventist Church Manado - Kasingku, Juwinner Dedy (Klabat Theological Review, 2021)
This research utilizes a quantitative design in which measurements are used to see the level of variables and to see the relationships and effects of two or more variables for statistical studies. Convenience sampling is the data collection process. To locate the quantitative data, the questionnaire instrument is used. The interpretation of church members returning the tithe in this study used a Likert scale. There are three views of church members on the returning of the tithe as a result of this research. The first is the determination of members of the church to return the tenth because of the commandments of God is very high. The second is the belief of members of the church to return the tithe based on confidence in the organization of the church is high. The third is that by returning the tithe, church members believe they will receive God's blessings is very high. Key Words: God’s commend; church organization, blessing; tithe   References Babbs, Arthur V. The Law of the Tithe. New York, Fleming H. Revell Company, l9I2. Merriam-Webster.com Dictionary , s.v. “tithe ,” accessed February 23, 2021, https://www.merriam-webster.com/dictionary/tithe . Miller, A. W. The Law of the Tithe and of the Free-Will Offering . Columbia, SC: Presbyterian Publishing House, 1873. Moleong, Lexy J. Metodelogi Penelitian Kualitatif .  Bandung: Remaja Rosdakarya, 2017. Nolan, Michael and Hartigan, An Enquiry Into the History Of Tithe, Its Influence Upon The Agriculture, Population and Morals of Ireland: With A Plan For Modifying That System. Charleston, SC: Nabu Press, 2011. Rolston, Holmes. Stewardship In the New Testament Church: A Study in the Teachings of Saint Paul concerning Christian Stewardship . Eugene, OR: Wipf and Stock Publishers, 2016. Seventh-day Adventist Believe . Ministerial Association: General Conference of Seventh-day Adventists, 2005. Seventh-day Church Manual. Washington, DC: Review and Herald Publishing Association, 2015. Suryoatmono, B. Kursus Statistika Dasar. Adapted from http://home.unpar.ac.id/ ~suryoatm/Kursus%20Statistika%20Dasar.PDF. 2007.  Suharsimi, Arikunto.  Pengertian instrument menurut para ahli (2015) adapted from https ://www.seputarpengetahuan.co.id/2015/11/pengertian-instrumen-penelitian-menurut-para-ahli. White, Ellen Gould. Education. Mountain View, CA: Pacific Press Publishing Association, 1903. _______________. Patriarch and Prophet. Washington, DC: Review and Herald Publishing Association, 1890. _______________. The Review and Herald , Sept. 10, 1889.